Make Time for the Stars Fitting Astronomy into Your Busy Life - Cooke, Antony; SpringerLink (Online service) (New York, NY : Springer US, 2009)
Make Time for the Stars: Fitting Astronomy into Your Busy Life Antony Cooke Hungry for an opportunity to study the stars but have little or no time to do it? Then this book is for you! Perhaps you have a telescope from years ago, which you used a few times, then put it away in a closet, where it has been gathering dust ever since. Could you still use that telescope, or do you have to buy a new one? And what about all the gadgets on the market now? Which ones do you really need? About how much will it all cost you, and what should you look for when you finally have a night out to look? Antony Cooke will give you those answers, and outline a program for star (and Solar System) gazing that you will be able to fit into your busy life. He tells why it is imperative to get yourself the right equipment from the start (without breaking the bank!) and why he thinks it is important to focus on live viewing rather than fancy gadgetry and imaging techniques. Full of sound advice and lots of encouragement, you will come away from this book prepared to take up your old hobby with new vigor and finally get the pleasure you knew was possible from studying our neighbors in space.
The Busy Astronomer -- Making the Right Equipment Choices -- How to Expand Your Potential -- Maximizing Your Time at the Telescope -- The Moon -- The First Port of Call -- The Moon: Close Up and Personal -- Instant Imaging of the Moon -- The Lunar Terminator -- The Greater Solar System -- A Quick Guide to the Solar System -- Planetary Imaging on a Time Budget -- Spectacles in Our Neighborhood -- The Far In and Far Out -- Daytime Astronomy -- Deep Space -- Viewing Deep Space Objects -- Deep Space Imaging -- Astronomy via the Internet -- A Guide for Viewing Sessions.
Keywords: Physics; Observations, Astronomical; Astronomy -- Observations; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy; Electronic books